Pengembangan E-LKPD Berbasis Problem Based Learning pada Materi Sistem Pernapasan Manusia untuk Meningkatkan Pola Berpikir Kritis Siswa SMA Negeri 5 Kota Tanjung Balai - Arya, M.; Rahmadina, Rahmadina (Bioscientist : Jurnal Ilmiah Biologi, 2024)
Learning is a system consisting of several interrelated components (goals, materials, methods, learning evaluation). These components must be adjusted in the process of making a learning implementation plan. Students are guided to build their knowledge independently so that they can easily master the material obtained at school and then apply their knowledge in real life.Â  This research aims to develop an Electronic Student Worksheet (E-LKPD) based on Problem Based Learning (PBL) on the human respiratory system, with a focus on improving students' critical thinking patterns at SMA Negeri 5 Tanjung Balai City. The method used in this research is the 4-D model developed by Thiagarajan, which consists of four stages: Define, Design, Develop, and Dissemination. The research results showed that the developed E-LKPD received a very good feasibility assessment, with a percentage of 96.8% from material experts, 96.25% from media experts, and 96.6% from practitioner experts. From these results, it can be concluded that the PBL-based E-LKPD developed is valid, practical and effective for use in the learning process. It is hoped that this e-LKPD can increase student learning activities and help teachers convey material in a more interesting and interactive way.